1976
DOI: 10.1161/01.cir.54.4.671
|View full text |Cite
|
Sign up to set email alerts
|

Response to exercise in patients after total surgical correction of Tetralogy of Fallot.

Abstract: EXERCISE RESPONSE IN TF/James et al. 13. Daly WJ, Bondurant S: Direct measurement of respiratory pleural pressure changes in man. J AppI The patient and control groups, subdivided by sex and body surface area (BSA), were similar in height and weight. When comparing males to males and females to females with BSA 2 1.2 m2, maximal heart rates and working capacities were lower in the patient groups than in the control groups. An inverse relationship was observed between maximal working capacity and age at surgery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
1
1

Year Published

1980
1980
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(25 citation statements)
references
References 24 publications
3
20
1
1
Order By: Relevance
“…Several studies (2,6,11,15) have shown that cardiac output in intense exercise is lower in patients with total correction for tetralogy of Fallot due to a smaller stroke volume. As in the present study maximal heart rate has often been found to be lower (2,11,13), with the exception of the study by Mocellin et al (15). An impaired cardiac output may be partially compensated for by an increase in maximal arteriovenous oxygen difference.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…Several studies (2,6,11,15) have shown that cardiac output in intense exercise is lower in patients with total correction for tetralogy of Fallot due to a smaller stroke volume. As in the present study maximal heart rate has often been found to be lower (2,11,13), with the exception of the study by Mocellin et al (15). An impaired cardiac output may be partially compensated for by an increase in maximal arteriovenous oxygen difference.…”
Section: Discussioncontrasting
confidence: 83%
“…Several postoperative studies have shown that the majority of patients can enjoy a normal life without symptoms (9,14) and have a fair tolerance to physical exercise (2,6,7,11,13,15). However, hemodynamic and angiographic studies at rest (3.…”
Section: Introductionmentioning
confidence: 99%
“…119 Postoperative studies of patients with coarctation of the aorta or tetralogy of Fallot have demonstrated findings consistent with underlying ventricular dysfunction. 120,121 These observations should be kept in mind when such patients are evaluated before noncardiac surgery. Patients receiving primary cardiac repair at a younger age in the present era may be less prone to postoperative ventricular dysfunction because of improved surgical techniques.…”
Section: Pulmonary Vascular Disease and Congenital Heart Diseasementioning
confidence: 99%
“…117 Postoperative studies of patients with coarctation of the aorta or tetralogy of Fallot have demonstrated findings consistent with underlying ventricular dysfunction. 118,119 These observations should be kept in mind when such patients are evaluated before noncardiac surgery. Patients receiving primary cardiac repair at a younger age in the present era may be less prone to postoperative ventricular dysfunction because of improved surgical techniques.…”
Section: Pulmonary Vascular Disease and Congenital Heart Diseasementioning
confidence: 99%